Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I got this question in a practice book.

A,B,C and D are $n\times n$ matrices with non-zero determinant.

$ABCD = I$ , then $B^{-1}$ = ?

The answer to this was $B^{-1}= CDA$.

How was that answer arrived at ?

share|improve this question
add comment

6 Answers

up vote 10 down vote accepted

$ABCD=I$, $BCD=A^{-1}$, $CD=B^{-1}A^{-1}$, $CDA=B^{-1}$.

share|improve this answer
    
Wow if you put it that way it makes a lot of sense , Thanks –  mataug Mar 7 '13 at 1:01
add comment

$(AB)(CD)=I \Rightarrow (CD)(AB)=I \Rightarrow (CDA)(B)=I \Rightarrow CDA=B^{-1}$.

Edit: Alternatively, $(A)(BCD)=I \Rightarrow (BCD)(A)=I \Rightarrow (B)(CDA)=I \Rightarrow CDA=B^{-1}$.

share|improve this answer
    
That's from far my favorite answer here, +1. –  1015 Mar 7 '13 at 2:08
    
+1: Me too... ${}{}{}$ –  copper.hat Mar 7 '13 at 3:37
add comment

Since A, B, C, D all have non zero determinant this implies that their respective inverses exist.

It's really an exercise in matrix algebra and in particular matrix multiplication.

\begin{align} ABCD &=I\\ AB &=D^{-1}C^{-1}\\ B &=A^{-1}D^{-1}C^{-1}\\ B^{-1} &=CDA \end{align}

share|improve this answer
1  
Aah, an important point to solving objective questions, "Since A, B, C, D all have non zero determinant this implies that their respective inverses exist." . Thanks . –  mataug Mar 7 '13 at 1:09
add comment

If $ABCD = I$, then $BCD = A^{-1}$, $BC = A^{-1}D^{-1}$, $B = A^{-1}D^{-1}C^{-1}$, from which we get $B^{-1} = (A^{-1}D^{-1}C^{-1})^{-1} = CDA$.

share|improve this answer
    
This a bit more complicated, but still good to know . Thanks. –  mataug Mar 7 '13 at 1:04
add comment

If $ABCD = I$, then we could find a somewhat cyclic relation between these matrices: $$ ABCDA = A \Rightarrow BCDA = A^{-1}A=I $$ by exploiting multiplication from left or right, in addition to that matrix and the inverse of a matrix can commute in a multiplication.

Doing the same trick leads us to: $CDAB = I, DABC = I$ also.

$BCDA = B(CDA)=I$ and $CDAB = (CDA)B = I$ give you the answer.

share|improve this answer
add comment

Suppose $A$ is a $n \times n$ matrix with non-zero determinant and $AB=I$. Then we can say that $B$ is the inverse of $A$, and we can say that $B^{-1}=A$?

Using the same rules for $ABCD=I$, partion it in $(ACD)B=I$ and let $ACD=X$ so $XB=I$. Thus we can say that $B^{-1}=X$. Thus $B^{-1}=ACD$.

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.